Efeitos de múltiplos treinos discriminativos sobre tarefas de resolução de problema - Gaiato, Mayra Helena Bonifacio (2010)
This research set up a successive discrimination repertoire and tested its functionality to solve two problems. Seven children underwent a sequence of five simultaneous discrimination tasks in which pairs of stimuli varied in two dimensions. The tasks followed a sequence in which the dimensions used were of an easier discrimination by children (i.e. color and shape) until reach a discrimination in which both dimensions were more difficult for children (thickness and orientation). In between each discrimination task, a reversal intradimension task has merged, where the SD became SK and vice versa, without signaling. Having completed this reversal task, a new discrimination task was showed, again without signaling, with a new pair of stimuli, which varied in two dimensions. The aim of the training, prepared in this order, was to create in the children a story of discriminated extinction. This extinction is capable of generating variation, favoring the occurrence of a faster discrimination from one training to another and increases in attentional control, which generates a reason for the children s answer. The effects of this experimental historic were evaluated in two problem solving tasks: logical blocks grouping and tangran figures assembly. The logical blocks set was effective to evaluate the role of discriminative training in children s behavioral repertoire. The post-test results showed that the participant s stimulus control on the dimensions of the stimuli is enhanced. The results of the post-test with the tangram indicated that, with a possible exception of one child, it is not possible to affirm on behalf of a beneficial effect of discriminative training in orientation to the assembly of the tangram